Global Medicines Regulation in Pregnancy and Lactation: Addressing Emerging Therapies, Safety, and Access Inequalities - Abdelrahman, Riad Mohammed; Musa, Taha Hussein; Arbab, Ismail Adam; Suliman, Mohsen Hussein; Khalifa, Ala Gamaleldin; Ahmed, Eltieb Omer; Gasmallah, Sahar Ibrahim; Ahmed, Wafaa Ramadan; Fadul, Khalid Hamid; Jalal, Mohammed (British Journal of Healthcare and Medical Research, 2025)
Safe medication use during pregnancy and lactation is fundamental to protecting maternal and neonatal health. However, global variability in regulatory frameworks, pharmacovigilance systems, and access to therapies presents major challenges-particularly for emerging treatments such as biologics, GLP-1 receptor agonists, and novel small molecules. This review aimed to synthesize international regulatory frameworks, evaluate safety monitoring practices, and explore disparities in access to medicines for pregnant and lactating populations. A narrative review was conducted using PubMed, Embase, Scopus, Web of Science, and regulatory agency websites (FDA, EMA, Health Canada, MHLW Japan, WHO), supplemented by pharmacovigilance databases (FAERS, VigiBase, EudraVigilance). Publications in English from 2000-2025 addressing regulatory policies, safety monitoring, or access inequalities were included. Extracted data were analyzed to identify global trends, gaps, and best practices in maternal-fetal pharmacotherapy. High-income countries demonstrate mature systems, including the FDA Pregnancy and Lactation Labeling Rule, EMA risk management plans, and comprehensive pharmacovigilance infrastructures. In contrast, low- and middle-income countries (LMICs) often face fragmented regulations, limited monitoring capacity, and restricted access to innovative therapies. Global initiatives such as the World Health Organization (WHO) guidelines, the International Council for Harmonization (ICH) E11(R1) guideline, and TransCelerate programs promote harmonization, yet substantial gaps remain. Active and passive surveillance mechanisms, pregnancy registries, and real-world data enhance safety assessment for emerging therapies, while access inequalities persist due to regulatory delays, cost, and sociocultural barriers. Despite meaningful advances in high-resource settings, LMICs continue to experience major challenges in ensuring safe and equitable access to medicines. Strengthening evidence-based, harmonized regulatory frameworks, expanding pharmacovigilance coverage, and integrating real-world evidence are essential to safeguarding maternal and neonatal health. Coordinated global collaboration is imperative to achieve equitable access to innovative therapies worldwide.